Selected aspects of attempted suicides. (1st March 2011) - de Silva, P; de Silva, D; Jayasinghe, S; de Alwis Seneviratne, R; Abeyratne, M; Rajapakse, D; Mendis, N
Abstract : Objectives: To describe selected aspects of attempted suicides. Methods: From 668 presented with attempted suicides presented to National Hospital of Sri Lanka (April to December 2002), 300 were randomly selected and interviewed using a pretested questionnaire. Results: All confessed that at the time of the incident they really wanted to die. In 134 (45%) instances no one was present at the time of the incident and 225 (75.5%) made the attempt without prior planning. After the attempt 178 (60.1%) notified a potential helper. Majority (190, 63.8%) had not communicated regarding the intention to harm at any time before the incident. When asked about the chances of death 132 (44.7%) informed that death was probable or certain. Most (268, 90.5%) of the incidents did not have an association with alcohol or drug use. Interpersonal conflicts were the precipitating cause in 230 (76.6%). Conclusion: Even though at the time of the event all wanted to die majority had notified after the event. Most have not communicated the need to die at any time before the incident. Most acts were done without prior preparation. Interpersonal conflicts were the commonest precipitating cause.